The impact of mining activity on water quality at Tasik Chini - Shahfina , Mohd Jaafar (2013)
The purpose of this study is to study the impact of mining activity on water quality at Tasik Chini. Six sampling stations were chosen at Tasik Chini, there are Laut Gumum, Laut Jerangking, Laut Kenawar, Laut Melai, Pulau Bali/PLKN and Tasik Chini Resort. Twenty-six parameters were analyzed based on in-situ and laboratory test and all parameters were analyzed according to National Water Quality Standard for Malaysia (NWQS) and Water Quality Index (WQI). Twelve of from the parameters which are heavy metals concentration (Na, Mg, K, Ca, Fe, Co, Ni, Cu, Zn, Cd, Pb, Sb) were analyzed by run ICP-MS test. Results indicate that low concentration found in water sample. Most of heavy metal concentration increase during wet day but still classified in Class I. Only for Fe at Pulau Balai/PLKN and Cd at Laut Kenawar during wet day classified in Class II. According to the National Water Quality Standard for Malaysia, electrical conductivity (EC), ammoniacal nitrogen (NH3-N), Phosphate, Nitrate, total suspended solid (TSS) were classified under Class I, while pH, turbidity, biochemical oxygen demand (BUD), chemical oxygen demand (COD) and total coliform were classified under Class II. For dissolved oxygen (DO) most were classified under Class III but there are two station which are Laut Jerangking and Laut Kenawar during dry day were classified under Class IV. The temperature was within the normal ranges. According to Water Quality Index (WQI), the water at Tasik Chini was classified under Class II, meaning it is suitable for recreational and safe for body contact. Based on result, mining activity is not the main source of pollution at Tasik Chini because low concentration of heavy metal were obtained from the test. Other activities such as agriculture and longing contributed the pollution of water at Tasik Chini.